Affektive Reaktionen und motorisches Lernen in einer Wettkampfsituation: Vorläufige Ergebnisse einer experimentellen Studie [Affective reactions and motor learning in a contest situation: Preliminary results of an experimental study] - Steib, Simon; Braun, Sinja; Gegenfurtner, Paula; Schöttner, Hanna; Bettac, Marlene; Schuster, Lea; Wanner, Philipp; Köllner, Martin (53. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie, 2021)

Basic Human Body Dimensions Relate to Alcohol Dependence and Predict Hospital Readmission - Lenz, Bernd; Köllner, Martin; Mühle, Christiane; Weinland, Christian; Kornhuber, Johannes (Journal of Clinical Medicine, 2019)
Alcohol dependence is a severe mental illness and there is a need for more effective preventive and therapeutic strategies. Translational research suggests that intrauterine sex hormone exposure modulates the risk and course of alcohol dependence during adulthood. During development, sex hormones permanently shape sexually dimorphic body dimensions. Thus, these dimensions may provide insight into sex hormone organization. Here, we compared body measurements (absolute, relative to, and residualized on height) between 200 alcohol-dependent in-patients and 240 age-matched healthy control subjects and investigated how these measurements associate with the patients' prospective 12- and 24-month outcome. The results show that alcohol dependence is related to lower absolute, relative, and residualized body measurements for height and weight, head circumference, bitragion head arc, lip-chin distance, hip, thigh, and calf circumference, and foot length and breadth. In male alcohol-dependent in-patients, higher risk, shorter latency, and more alcohol-related readmissions were predicted by higher absolute, relative, and residualized thigh and calf circumferences. The second-to-fourth finger length ratio, a putative proxy for prenatal sex hormone organization, was not convincingly correlated with the body dimensions, suggesting that the results represent pubertal (or later) effects. The study's findings have implications for further research. The body measurements' high accessibility may facilitate the future transition into clinical settings.
CRIS-Team WoS Importer:2020-01-28

Book review: An introduction to behavioral endocrinology (5th edition) - Köllner, Martin (Frontiers in Human Neuroscience, 2018)

Book Review: The Psychologist’s Companion (6th edition) - Schmiedl, Helena; Köllner, Martin (Frontiers in Psychology, 2019)

Commentary: Sexual dimorphism of facial width-to-height ratio in human skulls and faces: A meta-analytical approach - Köllner, Martin; Janson, Kevin; Schultheiss, Oliver (Frontiers in Endocrinology, 2018)

Das implizite Machtmotiv und Marker organisationaler Hormoneffekte: Zusammenhänge mit 2D:4D und fWHR [The implicit power motive and markers of organizational hormone effects: Associations with 2D:4D and fWHR] - Janson, Kevin; Bleck, Kira; Fenkl, Julia; Jägel, Franziska; Riegl, Lea T.; Köllner, Martin (36th Colloquium on Motivational Psychology, 2016)

Der Anreizwert eines Gesichts: Das implizite Machtmotiv und Aufmerksamkeitsorientierung [The incentive value of a face: The implicit power motive and attentional orienting] - Janson, Kevin; Köllner, Martin; Mair, Liane; Pülschen, Lea; Rudnaya, Alexandra; Schultheiss, Oliver (39th Colloquium on Motivational Psychology, 2019)

Die Implizit-Explizit-Profilkongruenz von Motiven: Ein studienübergreifender Test des Unabhängigkeitspostulats anhand von Bild- und Subkategorienprofilen innerhalb von Individuen [Implicit-explicit profile congruence of motives: A multi-study test of the independence postulate using within-individual picture and subcategory profiles] - Köllner, Martin; Rösch, Andreas G.; Schultheiss, Oliver (36th Colloquium on Motivational Psychology, 2016)

Evidence for a Robust, Estradiol-Associated Sex Difference in Narrative-Writing Fluency - Schultheiss, Oliver; Köllner, Martin; Busch, Holger; Hofer, Jan (Neuropsychology, 2021)
Objective: Despite evidence for an estradiol-linked sex difference in verbal fluency favoring women, recent reviews question this difference. We therefore examined the issue based on a narrative task that we have administered to different populations for over 20 years. Method: We meta-analyzed 98 studies (N = 11,528) conducted by our laboratories and that featured measures of biological sex and storytelling. We ran primary-data analyses (N = 797) on an overlapping subset of these studies that also included salivary hormone and digit ratio measures. Results: Women told longer stories than men, d = 0.31, 95% CI [0.24, 0.38], an effect that did not vary by geographic region but was moderated by cue type (verbal: d = 0.57, [0.44, 0.71]; pictures: d = 0.29, [0.22, 0.36]), response modality (oral: d = -0.04, [-0.18, 0.09]; handwriting: d = 0.39, [0.31, 0.47]; typing: d = 0.31, [0.21, 0.42]), and age (prepubertal children: d = 0.13, [-0.04, 0.30]; pubescents: d = 0.48, [0.23, 0.74]; premenopausal adults: d = 0.36, [0.29, 0.42]; postmenopausal adults: d = -0.09, [-0.35, 0.16]). Consistent with the age effect, estradiol, a sex-dimorphic hormone during the reproductive life stage, was a specific mediator of the sex difference in narrative-writing fluency. This mediation effect was moderated by prenatal hormone exposure, estimated via digit ratio. Conclusions: When verbal fluency is assessed through narrative writing, a robust female advantage becomes evident. It is associated with the reproductive life stage and variations in current estradiol concentrations, particularly in individuals prenatally exposed to relatively more estradiol than testosterone.
CRIS-Team WoS Importer:2021-05-28

"Evidence for a robust, estradiol-associated sex difference in narrative-writing fluency": Correction - Schultheiss, Oliver; Köllner, Martin; Busch, Holger; Hofer, Jan (Neuropsychology, 2021)
Reports an error in "Evidence for a robust, estradiol-associated sex difference in narrative-writing fluency" by Oliver C. Schultheiss, Martin G. Köllner, Holger Busch and Jan Hofer (Neuropsychology, 2021[Mar], Vol 35[3], 323-333). In the original article, there was an error in Table 1. The df for "18-50 years (adult men and premenopausal women)," originally read "1, 17," but should have read "1, 71." The online version of this article has been corrected. (The following abstract of the original article appeared in record 2020-71595-001). Objective: Despite evidence for an estradiol-linked sex difference in verbal fluency favoring women, recent reviews question this difference. We therefore examined the issue based on a narrative task that we have administered to different populations for over 20 years. Method: We meta-analyzed 98 studies (N = 11,528) conducted by our laboratories and that featured measures of biological sex and storytelling. We ran primary-data analyses (N = 797) on an overlapping subset of these studies that also included salivary hormone and digit ratio measures. Results: Women told longer stories than men, d = 0.31, 95% CI [0.24, 0.38], an effect that did not vary by geographic region but was moderated by cue type (verbal: d = 0.57, [0.44, 0.71]; pictures: d = 0.29, [0.22, 0.36]), response modality (oral: d = -0.04, [-0.18, 0.09]; handwriting: d = 0.39, [0.31, 0.47]; typing: d = 0.31, [0.21, 0.42]), and age (prepubertal children: d = 0.13, [-0.04, 0.30]; pubescents: d = 0.48, [0.23, 0.74]; premenopausal adults: d = 0.36, [0.29, 0.42]; postmenopausal adults: d = -0.09, [-0.35, 0.16]). Consistent with the age effect, estradiol, a sex-dimorphic hormone during the reproductive life stage, was a specific mediator of the sex difference in narrative-writing fluency. This mediation effect was moderated by prenatal hormone exposure, estimated via digit ratio. Conclusions: When verbal fluency is assessed through narrative writing, a robust female advantage becomes evident. It is associated with the reproductive life stage and variations in current estradiol concentrations, particularly in individuals prenatally exposed to relatively more estradiol than testosterone. (PsycInfo Database Record (c) 2021 APA, all rights reserved).
CRIS-Team Scopus Importer:2024-12-16

Exploratory evidence of sex-dimorphic associations of the ulna-to-fibula ratio, a potential marker of pubertal sex steroid exposure, with the implicit need for power - Köllner, Martin; Bleck, Kira (Adaptive Human Behavior and Physiology, 2020)

Face/Palm Measuring Tool: A stand-alone software for standardized hand and face morphometry [Software and manual] - Köllner, Martin; Schmiedl, Helena; Waßer, Julia; Schmiedl, Stefan (2017)

Implicit and explicit motive measures – A meta-analysis of their correlation and potential moderators of the relationship - Köllner, Martin; Schultheiss, Oliver (16th European Conference on Personality, 2012)

Implicit motives and the development of competencies: A virtuous-circle model of motive-driven learning. - Schultheiss, Oliver; Köllner, Martin (International handbook of emotions in education, 2014)
Keywords: implicit motives; implicit-explicit correlation; independence postulate; meta-analysis; motive congruence; picture-story exercise; questionnaire; self-attributed motivation

Inhibited power motivation is associated with the facial width-to-height ratio in females - Janson, Kevin; Bleck, Kira; Fenkl, Julia; Riegl, Lea T.; Jägel, Franziska; Köllner, Martin (Adaptive Human Behavior and Physiology, 2018)

Kodierung impliziter Motive in audiovisuellem Material – Erstellung von Übungs- und Kalibrierungsmaterial zur Coder-Zertifizierung und Vorstellung des MovieMotiveCoders [Coding implicit motives in audiovisual material – Constructing practice and calibration materials for coder certification and presentation of the MovieMotiveCoder] - Walther, Carola; Köllner, Martin (36th Colloquium on Motivational Psychology, 2016)

Korrelation impliziter und expliziter Motivmaße – Eine Metaanalyse [Correlation of implicit and explicit motive measures – A meta-analysis] - Köllner, Martin; Schultheiss, Oliver (2010)

Korrelation von Motivkongruenz und Wohlbefinden - Eine Metaanalyse [Correlation of motive congruence and well-being – A meta-analysis] - Köllner, Martin; Patalakh, Mariya; Schultheiss, Oliver (31st Colloquium on Motivational Psychology, 2011)

Korrelation zwischen Maßen impliziter und expliziter Motive – eine Metaanalyse - Köllner, Martin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)

Measuring Implicit Motives with the Picture Story Exercise (PSE): Databases of Expert-Coded German Stories, Pictures, and Updated Picture Norms - Schönbrodt, Felix D.; Hagemeyer, Birk; Brandstätter, Veronika; Czikmantori, Thomas; Gröpel, Peter; Hennecke, Marie; Israel, Laura S.F.; Janson, Kevin; Kemper, Nina; Köllner, Martin; Kopp, Philipp M.; Mojzisch, Andreas; et al. (Journal of personality assessment, 2020)
We present two openly accessible databases related to the assessment of implicit motives using Picture Story Exercises (PSEs): (a) A database of 183,415 German sentences, nested in 26,389 stories provided by 4,570 participants, which have been coded by experts using Winter’s coding system for the implicit affiliation/intimacy, achievement, and power motives, and (b) a database of 54 classic and new pictures which have been used as PSE stimuli. Updated picture norms are provided which can be used to select appropriate pictures for PSE applications. Based on an analysis of the relations between raw motive scores, word count, and sentence count, we give recommendations on how to control motive scores for story length, and validate the recommendation with a meta-analysis on gender differences in the implicit affiliation motive that replicates existing findings. We discuss to what extent the guiding principles of the story length correction can be generalized to other content coding systems for narrative material. Several potential applications of the databases are discussed, including (un)supervised machine learning of text content, psychometrics, and better reproducibility of PSE research.
CRIS-Team Scopus Importer:2020-04-03

Meta-analytic evidence of low convergence between implicit and explicit measures of the needs for achievement, affiliation, and power - Köllner, Martin; Schultheiss, Oliver (Frontiers in Psychology, 2014)
The correlation between implicit and explicit motive measures and potential moderators of this relationship were examined meta-analytically, using Hunter and Schmidt's (2004) approach. Studies from a comprehensive search in PsycINFO, data sets of our research group, a literature list compiled by an expert, and the results of a request for gray literature were examined for relevance and coded. Analyses were based on 49 papers, 56 independent samples, 6151 subjects, and 167 correlations. The correlations (?) between implicit and explicit measures were 0.130 (CI: 0.077-0.183) for the overall relationship, 0.116 (CI: 0.050-0.182) for affiliation, 0.139 (CI: 0.080-0.198) for achievement, and 0.038 (CI: -0.055-0.131) for power. Participant age did not moderate the size of these relationships. However, a greater proportion of males in the samples and an earlier publication year were associated with larger effect sizes. © 2014 Köllner and Schultheiss.
Keywords: Implicit motives; Implicit-explicit correlation; Independence postulate; Meta-analysis; Motive congruence; Picture-story exercise; Questionnaire; Self-attributed motivation

MMC: MovieMotiveCoder – A software for coding implicit motives and various behavioral data from audiovisual material [Software and manual] - Walther, Carola; Walther, Fabian T.; Köllner, Martin (2016)

Motivational standoff – Kodierung von impliziten Motiven in Videomaterial anhand von genereller Motivdichte, Motivprofilen und Clips zur Motivanregung in ausgewählten Filmen [Motivational standoff – Coding implicit motives in video material by determining overall motive density, motive profiles, and clips for arousing motives in selected movies] - Lorenz, Dorothea; Walther, Carola; Köllner, Martin (33rd Colloquium on Motivational Psychology, 2013)

Motive-Modulated Attentional Orienting: Implicit Power Motive Predicts Attentional Avoidance of Signals of Interpersonal Dominance - Janson, Kevin; Köllner, Martin; Khalaidovski, Ksenia; Pülschen, Lea Sarah; Rudnaya, Alexandra; Stamm, Laura; Schultheiss, Oliver (Motivation Science, 2021)
Implicit motives are commonly believed to orient behavior. Despite only sparse empirical evidence for this claim, an interplay of implicit motives and the attentional system seems plausible. In 2 preregistered eye-tracking studies (total N = 263 after exclusions), we tested whether the implicit power motive (nPower), the capacity to derive pleasure from having impact on others, measured via the Picture Story Exercise, predicted participants’ attentional orienting. Participants were simultaneously presented neutral faces and facial expressions of emotion (FEEs), with the latter signaling either dominance or submission. In both studies, nPower predicted initial avoidance of anger FEEs, which were deemed to be an aversive dominance signal. Initial orienting toward submissive FEEs was not predicted significantly by nPower. Results are discussed in the light of recent findings in neuroscience and with reference to limitations of our design. Our findings suggest that implicit motives do have an orienting function regarding initial responses to the encounter of interpersonal dominance signals.
CRIS-Team Scopus Importer:2021-12-17
Keywords: attentional orienting; eye-tracking; facial expressions of emotion; implicit motives; need for power

Organisierende Hormoneffekte auf das motivationale Gehirn [Organizing hormone effects on the motivational brain] - Köllner, Martin (39th Colloquium on Motivational Psychology, 2019)

Organizational effects of gonadal steroids on the implicit power motive - Janson, Kevin; Köllner, Martin; Schultheiss, Oliver (50th Conference of the German Society for Psychology, 2016)

Organizational hormone effects and reactions to a dominance contest: An experimental approach - Köllner, Martin; Braun, Sinja; Gegenfurtner, Paula; Schöttner, Hanna; Schuster, Lea; Steib, Simon (63. TeaP - Tagung experimentell arbeitender Psychologen, 2021)

Pubertäre organisierende Hormoneffekte: Gibt es einen Zusammenhang zwischen Gesichtsmerkmalen im Profil und dem impliziten Machtmotiv? [Pubertal organizing hormone effects: Is there a relationship between facial profile features and the implicit power motive?] - Gabduliyanova, Alisa; Riehlein, Lola; Theil, Florence; Steib, Simon; Köllner, Martin (39th Colloquium on Motivational Psychology, 2019)

Relationships of the Ulna-to-fibula Ratio to Baseline and Reactive Steroid Hormone Levels: An Exploratory Study - Köllner, Martin; Braun, Sinja; Schoettner, Hanna; Dlugash, Gelena; Bettac, Marlene; Steib, Simon (Adaptive Human Behavior and Physiology, 2022)
Objective Organizational hormone effects on the human brain and behavior are often retrospectively assessed via morphological markers of prenatal (e.g., 2D:4D digit ratio) or pubertal (e.g., facial width-to-height ratio, fWHR) hormone exposure. It has been argued that markers should relate to circulating hormones particularly in challenging, dominance/status-relevant situations. However, meta-analytic research indicates that fWHR, a frequently used pubertal marker, is neither reliably sex-dimorphic nor related to steroid hormones. This casts doubt on fWHR's validity for reflecting hormone levels. Ulna-to-fibula ratio (UFR), an alternative, long-bone-length-based pubertal marker, is sex-dimorphic and associated with dominance motivation. However, its hormonal associations were never tested before. We therefore explored UFR's relationships to baseline and reactive hormone levels. Methods We measured ulna and fibula length as well as shoulder/waist/hip circumference of 81 participants (49 women; after exclusions) via anthropometry. Salivary hormone levels (estradiol, testosterone) at baseline and after a gross-motor one-on-one balancing contest were measured via radioimmunoassay. Results We replicated UFR's dimorphism, unrelatedness to height, and correlations to other putative markers of organizational hormone effects. On an exploratory basis, we found UFR to be related to overall baseline testosterone and to competition-induced reactive surges in steroid hormones (estradiol, testosterone) overall and in women. Conclusions Our results hint at UFR's relationship to baseline testosterone and may indicate functional connections between outcomes of pubertal organizational hormone effects and contest-induced steroid reactivity. Pubertal organizational hormone effects may prepare the endocrine system for dominance and status contests. However, the small sample and the exploratory nature of our research demands replication.
CRIS-Team WoS Importer:2022-09-09

Skalierungseffekte von Motiven auf implizites Lernen – Beeinflussen unsere impliziten und expliziten Motive die Lernleistung? [Scaling effects of motives on implicit learning – Do our implicit and explicit motives influence learning performance?] - Köllner, Martin (33rd Colloquium on Motivational Psychology, 2013)

Stärke und Vorbedingungen von Motivanregungseffekten: Eine meta-analytische Bestandsaufnahme [Size and preconditions of motive arousal effects: A meta-analytic summary] - Heyd, Corinna; Schultheiss, Oliver; Köllner, Martin (39th Colloquium on Motivational Psychology, 2019)

The implicit power motive and the facial width-to-height ratio as possible marker of organizational hormone effects during puberty - Janson, Kevin; Bleck, Kira; Fenkl, Julia; Riegl, Lea T.; Jägel, Franziska; Köllner, Martin (47th Annual Meeting of the International Society of Psychoneuroendocrinology, 2017)

The implicit power motive and the facial width-to-height ratio as possible marker of organizational hormone effects during puberty - Janson, Kevin; Bleck, Kira; Fenkl, Julia; Riegl, Lea T.; Jägel, Franziska; Köllner, Martin (Psychoneuroendocrinology, 2017)

The influence of implicit motives on implicit instrumental conditioning: Testing a principle focusing on the power motive - Köllner, Martin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

The social biopsychology of implicit motive development - Köllner, Martin; Janson, Kevin; Bleck, Kira (Routledge International Handbook of Social Neuroendocrinology, 2019)
CRIS-Team WoS Importer:2020-01-17

The sociobiological development and arousal of implicit motives: The emergence of a growth-and-prune model of motive development and the continued linkage of hormones and motives throughout the life span - Köllner, Martin; Janson, Kevin (47th Annual Meeting of the International Society of Psychoneuroendocrinology, 2017)

The sociobiological development and arousal of implicit motives: The emergence of a growth-and-prune model of motive development and the continued linkage of hormones and motives throughout the life span - Köllner, Martin; Janson, Kevin (Psychoneuroendocrinology, 2017)

The Ulna-to-Fibula Ratio as a Marker of Organizational Hormone Effects on Implicit Motive Development: A High-Powered Preregistered Replication - Köllner, Martin; Puelschen, Lea-Sarah; Stamm, Laura; Janson, Kevin (Motivation Science, 2022)
This preregistered study (N = 250; 148 women; after exclusions) aimed at replicating findings by Kollner and Bleck (2020) regarding relationships of the implicit power motive (nPower) and activity inhibition with their proposed new marker of pubertal organizational hormone effects, the ulna-to-fibula ratio (UFR). Our cross-sectional design included the Picture-Story Exercise (nPower, activity inhibition) and anthropometry of ulna and fibula length, facial width and height, shoulder/waist/hip circumference, and 2D:4D digit ratio. As a validation check for organizational hormone effects' relationships to motivation, we tested UFR's sex-dimorphism, independence of body height, and interrelationships with other markers. Results showed that the validation check was successful. UFR was sex-dimorphic, independent of body height, and significantly associated with other possible markers of pubertal organizational hormone effects, including facial width-to-height ratio, waist-to-hip ratio, and shoulder-to-hip ratio. As predicted, a "sex-typical" UFR, low for women and high for men, was associated with the inhibited power motive (outliers excluded). nPower's sex-dimorphic relationship with UFR reported by Kollner and Bleck (2020) was not replicated. UFR's relationship with the inhibited power motive, in conjunction with findings by Schultheiss et al. (2019) for prenatal organizational hormone effects, add to accumulating first evidence for hormonal contributions to implicit motive development but also call for larger-sample replication.
CRIS-Team WoS Importer:2022-07-01

Zusammenhänge zwischen dem impliziten Machtmotiv, Steroidhormonen und Längen der Ulna und Fibula [Relationships between the implicit power motive, steroid hormones, and length of ulna and fibula] - Bleck, Kira; Fenkl, Julia; Jägel, Franziska; Köllner, Martin (36th Colloquium on Motivational Psychology, 2016)